Multidisciplinary outpatient care program for patients with chronic low back pain: design of a randomized controlled trial and cost-effectiveness study [ISRCTN28478651] - Anema Johannes R; Lambeek Ludeke C; van Royen Barend J; Buijs Peter C; Wuisman Paul I; van Tulder Maurits W; van Mechelen Willem (BMC, 2007)
Abstract Background Chronic low back pain (LBP) is a major public and occupational health problem, which is associated with very high costs. Although medical costs for chronic LBP are high, most costs are related to productivity losses due to sick leave. In general, the prognosis for return to work (RTW) is good but a minority of patients will be absent long-term from work. Research shows that work related problems are associated with an increase in seeking medical care and sick leave. Usual medical care of patients is however, not specifically aimed at RTW. The objective is to present the design of a randomized controlled trial, i.e. the BRIDGE-study, evaluating the effectiveness in improving RTW and cost-effectiveness of a multidisciplinary outpatient care program situated in both primary and outpatient care setting compared with usual clinical medical care for patients with chronic LBP. Methods/Design The design is a randomized controlled trial with an economic evaluation alongside. The study population consists of patients with chronic LBP who are completely or partially sick listed and visit an outpatient clinic of one of the participating hospitals in Amsterdam (the Netherlands). Two interventions will be compared. 1. a multidisciplinary outpatient care program consisting of a workplace intervention based on participatory ergonomics, and a graded activity program using cognitive behavioural principles. 2. usual care provided by the medical specialist, the occupational physician, the patient's general practitioner and allied health professionals. The primary outcome measure is sick leave duration until full RTW. Sick leave duration is measured monthly by self-report during one year. Data on sick leave during one-year follow-up are also requested form the employers. Secondary outcome measures are pain intensity, functional status, pain coping, patient satisfaction and quality of life. Outcome measures are assessed before randomization and 3, 6, and 12 months later. All statistical analysis will be performed according to the intension-to-treat principle. Discussion Usual care of primary and outpatient health services isn't directly aimed at RTW, therefor it is desirable to look for care which is aimed at RTW. Research shows that several occupational interventions in primary care are aimed at RTW. They have shown a significant reduction of sick leave for employee with LBP. If a comparable reduction of sick leave duration of patients with chronic LBP of who attend an outpatient clinic can be achieved, such reductions will be obviously substantial for the Netherlands and will have a considerable impact. Trial registration ISRCTN28478651